2019
DOI: 10.3390/pr7070443
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Quality and Speed of Green New Product Development?

Abstract: With the deep integration of supply chain with Internet and Internet of things, it is an important way for enterprises to win market competition and seek sustainable development to develop green new products through external green supply chain integration (GSCI). This study established a unified research framework of external GSCI, knowledge spiral (KS), green new product development (NPD), and top management’s environmental awareness (TMEA). Structural equation modeling and analytic hierarchy process are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Lin et al [45] used the DEA model to evaluate the green innovation efficiency of the manufacturing industry. Yin et al [46] analyzed the influence of the relationship of green integrated supply chain in manufacturing enterprises on the quality and speed of green new product development. Ho et al [47] combined artificial neural networks (ANNs) and fuzzy rule sets to realize knowledge discovery and decision support in high-quality manufacturing using artificial intelligence.…”
Section: Green Innovation In the Manufacturing Industrymentioning
confidence: 99%
“…Lin et al [45] used the DEA model to evaluate the green innovation efficiency of the manufacturing industry. Yin et al [46] analyzed the influence of the relationship of green integrated supply chain in manufacturing enterprises on the quality and speed of green new product development. Ho et al [47] combined artificial neural networks (ANNs) and fuzzy rule sets to realize knowledge discovery and decision support in high-quality manufacturing using artificial intelligence.…”
Section: Green Innovation In the Manufacturing Industrymentioning
confidence: 99%
“…Therefore, some tests have been proposed to directly test the significance of the coefficient product ab, such as Sobel method, bootstrap method, product distribution method, and Markov Chain Monte Carlo (MCMC) method [45]. Due to higher power of bootstrap method [45], [46], bootstrap method was used to test the significance of mediating effect in this study. The mediating effect model is shown as follows where δ 0 denotes a constant, δ 1 − δ 9 denote regression coefficient of each variable, respectively, η it is an error term.…”
Section: ) Model For Examining Mediating Effectmentioning
confidence: 99%
“…Shi et al studied green design as an important part of GSCM [39]. Furthermore, Yin et al found that the integration of external green supply chain affects the quality and speed of green new product development [40]. Green production requires manufacturing enterprises to achieve environmental compatibility in the production process.…”
Section: Gbms Supply Chain Managementmentioning
confidence: 99%